Production potential of Plumbago zeylanica L. under different harvest schedules and crop geometry - S Singh, P B Kanjilal, Jinu Devi, Rumi Kotoky, R (Journal of Spices and Aromatic Crops, 2004)
A field experiment on Plumbago zeylanica with three plant densities, namely, 4.9 m-2, 2.7 m-2 and 1.2 m-2 and three harvesting schedules, namely, after first year, second year and third year, was conducted during 1999-2001 at Jorhat (Assam). Plant density significantly influenced number of branches plant-1, shoot and root biomass plant-1 and total yield of roots ha-1. Plant height was found to reduce with the age of the plant. The total dry'root yield was maximum in the plant density 2.7 m-' (5.2 t ha-1). The yield attributing characters, namely, number of branches plant-1 (25.6), shoot biomass plant-1 (408.2 g), root biomass plant-1 (607.4 g) and total root yield (7.1 t ha-1) were maximum when harvested at third year. Maximum phenol, carbohydrate and protein contents were recorded in roots (5.06%, 31.70% and 13.04%, respectively) and leaves (3.40%, 10.60% and 7.84 %, respectively) of plants harvested during the third year.